Application of Forecasting and EOQ Methods as an Effort to Control Raw Material Inventory for Implora Lip Cream Products - Ni Luh Putu Hariastuti; Vegha Swastiana Widyawati (SAINTEKS : Jurnal Sain dan Teknik, 2026)
The phenomenon of the rapidly growing cosmetics industry in Indonesia aligns with Indonesia's growing population and increasingly diverse needs. Implora Sukses Abadi Company, as a cosmetics company, plays an important role in the growth of this industry through its flagship lip cream. The high consumer demand for lip cream often cannot be met due to limited supply. Therefore, the Company must plan to control inventory by applying forecasting methods to predict the amount of lip cream production in the future period. Quantitative forecasting based on historical data from lip cream production results is used, and inventory control is implemented using the economic order quantity (EOQ) method. Based on the results of this study, the exponential smoothing method was the best forecasting tool, with the smallest MSE of 453,332.6. This is supported by other error value indicators that also achieve the smallest values, such as the MAD and MAPE, at 1,226.364 and 51.613, respectively. The optimal policy for the amount of inventory control costs for each raw material was obtained: PURI of Rp. 858,724,170; raw material CSM22 of Rp. 543,696,239, BORD4 raw materials amounting to Rp. 448,740,905, SBSL raw materials amounting to Rp. 93,913,823, CPR8 raw materials amounting to Rp. 411,278,008, and BTM03 raw materials amounting to Rp. 317,308,683.